GIS-material for the archaeological project: Kv Banken 1 - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
A preliminary investigation was performed in the Banken block in central Linköping by the Swedish National Heritage Board's contract archaeology division, UV Öst, due to planned construction of buildings. The investigation included the study of maps and archives as well as excavation and the purpose was to examine whether any cultural layers were preserved. No cultural layers were found during the excavation in June 2005. A complementary investigation of the mid part of the block was performed in June 2007, in connection with the demolition of the existing houses. Neither here were any cultural layers found. Finally, a small scale documentation has been made of cultural layers on the Klostergatan and Borgmästaregatan streets, in connection with sheet piling and trenching for district heating.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the preliminary investigation was to deepen the knowledge acquired from earlier surveys and to conclude whether or not there are any preserved cultural layers in the area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Den arkeologiska förundersökningen inom kv Banken 1 i centrala Linköping, utfördes av Riksantikvarieämbetet UV Öst inför planerad nybebyggelse. Undersökningen omfattar kart- och arkivstudium samt en arkeologisk undersökning, med syfte att konstatera om eventuellt äldre kulturlager fanns bevarade. Inga kulturlager kunde hittas vid undersökningen i juni 2005. En kompletterande förundersökning genomfördes i juni 2007 i kvarterets mellersta del, i samband med rivningen av befintliga byggnader. Inte heller här fanns några bevarade äldre kulturlager. Slutligen har en mindre dokumentation av kulturlagerrester gjorts vid schaktningar i Klostergatan och Borgmästaregatan, i samband med schaktning för spontning och anslutning till fjärrvärme.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Målsättningen med den nu aktuella förundersökningen var att fördjupa den tidigare kunskapsbilden och att konstatera om det finns bevarade kulturlager eller ej.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Kv Banken 1
Keywords: historical period; historisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive